2003
DOI: 10.1097/00005537-200306000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Facial Pain or Headache and Computed Tomography in Rhinosinusitis in Canadian and U.S. Subjects

Abstract: There was no correlation between pain severity and disease severity by sinus CT scan as graded by the Lund-McKay, Harvard, or Kennedy staging system. Facial pain and headache, although frequent complaints of patients with rhinosinusitis, are not useful predictors of sinus disease severity. There appears to be a difference in pain perception between the two North American populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 9 publications
(6 reference statements)
2
42
3
2
Order By: Relevance
“…Our results are in concordance with studies in sinusitis patients, showing no association between headache/facial pain and opacification of the paranasal sinuses at CT (10,13). In these studies, headache was not differentiated into migraine or TTH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in concordance with studies in sinusitis patients, showing no association between headache/facial pain and opacification of the paranasal sinuses at CT (10,13). In these studies, headache was not differentiated into migraine or TTH.…”
Section: Discussionsupporting
confidence: 92%
“…The few that exist have either included a selected group of patients (10,11), have not included a control group (12), or have not differentiated between migraine and tension-type headache (TTH) (11,13).…”
Section: Introductionmentioning
confidence: 99%
“…Basu et al 17) reported that symptoms based on the Sinonasal Assessment Questionnaire in a CRS group had no correlation with the objective status based on Lund-Mackay CT score. Shields et al 18) also found that facial pain or headache in CRS subjects and disease severity by sinus CT scan had no correlation. This is because CRS affects patients significantly, but a patient's suffering is subjective and may not be proportionate to severity.…”
Section: Discussionmentioning
confidence: 97%
“…A coronal sinus CT was used to evaluate the evidence of acute-on-chronic rhinosinusitis, to evaluate isolated or diffuse mucosal thickening of frontal sinus and also to planning the surgical approach. On evidence of CT we also completed preoperatively Lund-Mackay score for each patients but we consider that there is not correlation between pain severity and disease severity by CT scan as reported in the literature [9].…”
Section: Methodsmentioning
confidence: 99%